Unraveling Consumer Mindset: Analysis of Consumer Behavior in the Distribution of E-WOM on The Originote Skincare Product - Nurul Qurrotul Aini; Fadhilah Nur Oktaviani; Sudarmiatin Sudarmiatin (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the spread of e-WOM on the skincare brand "The Originote" through the use of qualitative methods with a case study approach, as well as data collection techniques in the form of interviews and documentation. The results of the analysis show that The Originote has succeeded in managing the spread of e-WOM well, thus contributing to high levels of consumer satisfaction and loyalty. This is evidenced by positive assessments on various platforms such as TikTok and Shopee, as well as a strong tendency among consumers to make repeat purchases and recommend this skincare to others. This study is expected to provide strategic recommendations to Originote to increase consumer participation so that they are willing to be involved in e-WOM and increase insight into other brands about the importance of managing e-WOM properly to avoid losing consumer trust and buying interest.